Hendrik Birus's "The Archeology of 'Humanism'": Roundtable Discussion - Adams, Hazard; Behler, Ernst; Birus, Hendrik; Derrida, Jacques; Iser, Wolfgang; Krieger, Murray; Miller, Hillis; Pfeiffer, Ludwig; Readings, Bill; Wang, Ching-hsien; Yu, Pauline (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
This roundtable discussion of "The Archeology of 'Humanism'", Hendrik Birus's contribution to the first International Conference for Humanistic Discourses, was held in April, 1994. The papers of this first meeting of the ICHD have been published in volume 4 of Surfaces (1994).